4x+2=-7x+2

Simple and best practice solution for 4x+2=-7x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+2=-7x+2 equation:


Simplifying
4x + 2 = -7x + 2

Reorder the terms:
2 + 4x = -7x + 2

Reorder the terms:
2 + 4x = 2 + -7x

Add '-2' to each side of the equation.
2 + -2 + 4x = 2 + -2 + -7x

Combine like terms: 2 + -2 = 0
0 + 4x = 2 + -2 + -7x
4x = 2 + -2 + -7x

Combine like terms: 2 + -2 = 0
4x = 0 + -7x
4x = -7x

Solving
4x = -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
4x + 7x = -7x + 7x

Combine like terms: 4x + 7x = 11x
11x = -7x + 7x

Combine like terms: -7x + 7x = 0
11x = 0

Divide each side by '11'.
x = 0

Simplifying
x = 0

See similar equations:

| a/5-6=9 | | 2+8(7+x)=83 | | 7(6-6m)=336 | | x^2-2xy+y^2-x=0 | | 6(5-7p)=-264 | | -5+5x=3x-9 | | 252=7(1-5r) | | 3.55+4=22 | | 0.25y+1.5+3=1y-4.5-3 | | x^2+14x-91=4 | | -6(p+8)+4p=-33+3p | | 5-7x=6x+70 | | -4-4v=-3(2v-4) | | -7(v+2)=-14-7v | | 5x-3-3x=3-x | | 495=(x+2)(x)(5) | | -4x-7=2x-49 | | -7+3(3b-5)=-26+8b | | 4(x+3)+7-8x=3 | | 247=2-7(-3-8k) | | 1/3m-7/8=4/9 | | -6x+5=45+4x | | 32+(18-6)/2= | | 1/-7/8=4/9 | | 60+(25-10)/5= | | 3x-6(19)=48 | | 4x+1-x=-23 | | -(6x-5)-(2x-5)+9=-8(x-1)-(4x+8)+3 | | 56+(40-12)/4= | | 9x-23=x+1 | | xsquared+9x+16=8 | | 3+2x=3(2+x) |

Equations solver categories